The role of BBBEE in Enterprise and Supplier Development in the South African construction industry : the case of Aveng - Garrine, Vusani (My University, 2015)
Due to the legacy of apartheid, where black people have been economically excluded from participating in business ventures on an equal basis with predominantly medium to large white owned entities, the government’s Revised Broad-based Black Economic Empowerment (BBBEE) codes of Good Practice aim to assist in redressing the effects of apartheid by setting higher compliance targets in relation to Enterprise and Supplier Development programmes. It is therefore critical that enterprise and supplier development initiatives in the construction sector in South Africa are evaluated to establish whether they do assist in fostering economic development as envisaged by the government. This study will evaluate the impact of Broad Based Black Economic Empowerment on SMMEs in the South African Construction industry by evaluating the Enterprise and Supplier Development Programme at the Aveng Group. With the use of Interviews, the experiences and perceptions of various stakeholders regarding the benefits and sustainability of the Aveng Group’s Enterprise & Supplier Development programme will be provided. The Aveng Group, which is the largest construction company in South Africa by revenue and diversification, was used as a case study. While large companies such as Aveng continue to attain very high BBBEE scores, the actual industry is not transforming at the required rapid rate and suppliers who participate in these processes do not necessarily remain sustainable due to the short term nature of construction projects. There are a number of key findings derived from the study: There is a lack of supplier diversity in relation to the number of small enterprises which have benefitted from ESD programmes. Suppliers who have attained long term supply contracts are those who have enjoyed long term relationships with individuals in the large companies or are themselves former employees of those iii companies. This indicates that narrow based BBBEE spans further than the ownership scorecard element where it is more prevalent. There is a tendency by large companies to simply engage in tick box exercises instead of embracing the spirit of transformation. This practice only assists the large companies in terms of securing lucrative government contracts and also only with compliance without any sustainable value. A challenge is faced by policy makers as well as large organisations where there is a lack of quality small businesses that are able to provide high value and highly technical services which large infrastructure projects require. While there are challenges with factors such as fronting, lack of support, lack of procurement opportunities as well as insufficient financial support, this research has shown that the Enterprise and Supplier Development programmes do result in sustainable benefits for the large organisations as well as the beneficiaries and small enterprises if all the stakeholders; large companies, small companies as well as government agencies collaborate and have coherent strategies. The current BBBEE targets for preferential procurement as well as enterprise development have been proven to be relatively easy to attain. However, the Revised Codes of Good Practice aim to close that gap and will require more focused effort by large companies to attain the set targets.
Keywords: Affirmative action programs -- South Africa. Blacks -- South Africa -- Economic conditions.Construction industry -- South Africa.